Wódz doskonały w świetle łacińskich panegiryków późnoantycznych - Szopa, Adrian (Vox Patrum, 2015)
In this article I am describing how Roman panegyric’s writers of Late Antiquity (XII Panegyrici Latini, Claudius Claudianus, Sidonius Apollinaris, Flavius Merobaudes, Priscian, Ennodius, Corippus and others) presented an image of the perfect general with reference to their object of praise. On the ground of detailed analysis of those features I am going to indicate the most expected ones according to the social reception. Moreover, I will point out those means which were used by the authors to create the image of the ideal general. Next, I will pay attention to how the authors change their way in presenting the perfect general and how this development was connected with the general evolution of the genre. Lastly, I will answer a quite perverse question: if the perfect general could lead his soldiers to a victory in a real battle. In the background there will be a continuous question, if the panegyric – despite its limitation – can or can’t be treated as a valuable historical source.